Live poultry feeding and trading network and the transmission of avian influenza A(H5N6) virus in a large city in China, 2014–2015. (July 2021) - Zhang, Rusheng; Lei, Zhao; Liu, Chan; Zhu, Yuanzhao; Chen, Jingfang; Yao, Dong; Ou, Xinhua; Ye, Wen; Huang, Zheng; Luo, Li; Sun, Biancheng; Chen, Tianmu
Highlights: Live poultry markets (LPMs) are a source of avian influenza A(H5N6) virus in China. A mass of A(H5N6) viruses can be detected in the LPMs in Changsha, China. More stringent measures are required to prevent spread of H5N6 from LPMs. Abstract: Objectives: To understand the transmission mechanisms of the avian influenza A(H5N6) virus. Methods: This study explored the live poultry feeding and trading network (LPFTN) around Changsha city, China. Field epidemiological investigations were performed in Changsha to investigate the LPFTN with the environmental samples systematically collected during 2014–2015 to monitor and analyze the spread of the A(H5N6) virus. Two surveillance systems were also applied to find possible human cases of A(H5N6) infection. Result: The information of all the 665 live poultry farming sites, five wholesale markets, and 223 retail markets in Changsha was collected to investigate the LPFTN. Moreover, about 840 environmental samples were systematically collected from the LPFTN during 2014–2015 to monitor the spread of the A(H5N6) virus, with 8.45% (71/840) positive for the N6 subtype. Furthermore, the full genome sequences of 10 A(H5N6) viruses detected from the environmental samples were obtained, which were then characterized and phylogenetically analyzed with the corresponding gene segments of the A(H5N6) virus obtained from GenBank, to determine the source of human infection. Conclusion: It was demonstrated that the LPFTN provided a platform for the H5N6 transmission, and formed an infectious pool for the spread of the virus to humans.